Large-size flexible SiO2 aerogel composite board as well as preparation method and application thereof
By grafting long-chain flexible alkyl chains on silicone chains, large-size flexible SiO2 aerogel composite plates were prepared, which solved the problem of poor mechanical properties of aerogel materials and achieved high mechanical properties and large-size Preparation has promoted the industrialization of aerogel composite glass.
Patent Information
- Application Number
- CN202411605828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
The existing aerogel materials have extremely poor mechanical properties, making it difficult to prepare large-sized integrated aerogel plates, which limits the application range of aerogel composite glass in practical applications.
Using bifunctional 3-(2,3-epoxypropoxy)propyltrimethoxysilane as a silicon source, the long-chain flexible alkyl chain is grafted on the siloxane chain by reaction with bio-oleic acid to prepare A flexible composition is produced and a large-size flexible SiO2 aerogel composite plate is prepared by hydrolysis, molding, molding, aging and drying.
The mechanical properties, impact resistance and warping resistance of large-size SiO2 aerogel composite panels are improved, and the preparation of flat large-size aerogel plates is realized, and the industrialization of super energy-saving aerogel composite glass is promoted.
Smart Images

Figure CN119490344A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel preparation, and in particular to a large-size flexible SiO2 aerogel composite plate and a preparation method and application thereof. Background Art
[0002] At present, the building energy-saving glass with wide application and good energy-saving effect in the market mainly includes hollow glass and vacuum glass. However, hollow glass not only has poor thermal insulation and sound insulation, but also the air in the inner layer of the glass will condense or frost during use, which further reduces its performance; and the sealing and thermal insulation performance of vacuum glass in an alternating temperature difference environment gradually decreases, resulting in vacuum failure and loss of thermal insulation and sound insulation performance. In addition, the above two types of glass have poor fire resistance in the event of a fire, and are easy to burst when heated, which will cause serious harm to people's lives and property. Aerogel composite glass is a new type of building energy-saving material made by sandwiching an aerogel board between two pieces of glass and then vacuumizing and sealing. It has excellent insulation and sound insulation properties, good lighting and fire resistance, and has important application prospects in the future. However, due to the extremely poor mechanical properties of aerogel materials, it is difficult to prepare large-size (length * width * height: 200mm * 200 * 10mm or more) integrated aerogel boards, which limits the practical application of aerogel composite glass. Although some researchers have enhanced the mechanical properties of aerogels by using polyethylene glycol, polyvinyl alcohol and linear small molecule polymers, the preparation of large-sized aerogel sheets is still difficult to meet the requirements. Summary of the invention
[0003] To solve the above problems, the purpose of the present invention is to provide a large-sized flexible SiO2 aerogel composite board which is flat and large in size, has good flexibility, high mechanical properties, good impact resistance and warping resistance during drying, and a preparation method and application thereof.
[0004] The purpose of the present invention is achieved through the following technical solutions: A large-size flexible SiO 2 The aerogel composite board is obtained by sequentially hydrolyzing a flexible composition, gelling in a mold, demolding, aging and drying. The flexible composition is obtained by reacting the epoxy group on the siloxane chain in the silicon source with the carboxyl group of bio-based oleic acid, and grafting a long-chain flexible alkyl chain on the siloxane chain of the silicon source, wherein the silicon source is a bifunctional 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0005] A large-size flexible SiO 2 The preparation method of the aerogel composite plate comprises the following steps: S1. 3-(2,3-epoxypropoxy)propyltrimethoxysilane and bio-based oleic acid are mixed in proportion and stirred evenly, and then catalyst 1 for auxiliary grafting is added to react. After the reaction is completed, a colorless, transparent and viscous flexible composition is obtained.
[0006] S2. After the flexible composition, ethanol and water are mixed and stirred uniformly in proportion, hydrochloric acid is added to adjust the pH to 3-4, and hydrolyze to form silica sol.
[0007] S3. Add the silica sol to the catalyst 2 for assisting gelation and stir evenly, then pour it into a mold to react to obtain a gelled wet gel, then demold the wet gel and age and dry it to obtain a large-sized SiO 2 Aerogel composite panels.
[0008] Furthermore, the epoxy value of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.25 mol to 0.45 mol / 100g.
[0009] Furthermore, the bio-based oleic acid is any one of ricinoleic acid, lauric acid, Y-8 type vegetable oleic acid and Y-10 type vegetable oleic acid, and the acid value of the bio-based oleic acid is 160-175.
[0010] Furthermore, in step S1, the viscosity of the colorless, transparent and viscous flexible composition is 3000mPa.s-5500mPa.s, and the average molecular weight is 22000-38000.
[0011] Furthermore, the catalyst 1 is any one of sulfuric acid, zinc chloride and nitric acid.
[0012] Furthermore, in step S1, the mass ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to bio-based oleic acid is 1:(0.05-0.25).
[0013] Furthermore, in step S2, the mass ratio of the flexible composition, ethanol and water is 1:(5-9):(0.012-0.018).
[0014] Furthermore, the catalyst 2 is any one of ammonia water, tetramethylammonium hydroxide and sodium hydroxide.
[0015] Furthermore, in step S3, the mass ratio of the catalyst 2 to the silica sol is (0.005-0.02):1.
[0016] Furthermore, the aging in step S3 is to immerse the wet gel in ethanol for aging after demoulding, the immersion aging temperature range is 65-70°C, and the aging time range is 36-72h.
[0017] Furthermore, in step S3, the drying is carried out by supercritical CO 2 Dry, supercritical CO 2 Drying pressure is 7MPa~9MPa, CO 2The flow rate is 2500-2700 kg / h, the drying temperature is 55-60°C, and the drying time is 48h-72h.
[0018] A large-size flexible SiO 2 The application of aerogel composite plate is to use the large-size flexible SiO 2 Aerogel composite panels are used as sandwich materials for super energy-saving aerogel composite glass products.
[0019] In view of the problems of poor mechanical properties of silica aerogel and difficulty in drying large-sized integral molding, the present invention selects bifunctional 3-(2,3-epoxypropoxy)propyltrimethoxysilane as the silicon source, uses bio-based plant oleic acid as the modifier, and utilizes the epoxy group on the siloxane chain to react with the carboxyl group of bio-based oleic acid to graft long-chain flexible alkyl chains on the siloxane, thereby improving the flexibility of silica aerogel and improving the thermal conductivity of large-sized silica aerogel composite plates in supercritical CO 2 The impact resistance and warping resistance during the drying process can obtain a flat large-size silica aerogel composite plate, which greatly accelerates the industrialization of super energy-saving aerogel composite glass. Finally, the production process is simple and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0021] Figure 1 This is a diagram of the grafting reaction mechanism of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and oleic acid described in the present invention.
[0022] Figure 2 This is a diagram showing the gel reaction mechanism of the flexible composition of the present invention and catalyst 2.
[0023] Figure 3 The large-sized flexible SiO prepared in Example 1 of the present invention 2 Photo of aerogel composite board sample. DETAILED DESCRIPTION
[0024] The following is an explanation of the implementation of the present invention by specific specific embodiments. People familiar with the technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0025] like Figure 1-3As shown, a large-size flexible SiO2 aerogel composite board is obtained by hydrolyzing a flexible composition, gelling in a mold, demolding, aging and drying in sequence. The flexible composition is obtained by reacting the epoxy group on the siloxane chain in the silicon source with the carboxyl group of the bio-based oleic acid, and grafting a long-chain flexible alkyl chain on the siloxane chain of the silicon source, wherein the silicon source is a bifunctional 3-(2,3-epoxypropoxy)propyltrimethoxysilane. The epoxy value of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.25mol to 0.45mol / 100g. The bio-based oleic acid is any one of ricinoleic acid, lauric acid, Y-8 type vegetable oleic acid and Y-10 type vegetable oleic acid, and the acid value of the bio-based oleic acid is 160-175. The viscosity of the flexible composition is 3000m-5500mPa.s, and its average molecular weight is 22000-38000. The mass ratio of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane to the bio-based oleic acid is 1:(0.05-0.25). Example 2
[0026] This embodiment provides a large-size flexible SiO 2 The preparation method of the aerogel composite plate comprises the following steps: S1. After 3-(2,3-epoxypropoxy)propyltrimethoxysilane and silicic acid are mixed and stirred at a mass ratio of 1:0.2, sulfuric acid as a catalyst is added and reacted at 120°C for 48 hours to obtain a colorless, transparent and viscous flexible composition. The viscosity of the flexible composition is tested to be 4200 mPa.s and the average molecular weight is 32000.
[0027] S2. The flexible composition, ethanol and water are poured into a container in a mass ratio of 1:7:0.012, mixed and stirred evenly, and then 1 mol / L hydrochloric acid is added to adjust the pH to about 3-4, and hydrolyzed at 60° C. for 8 h to form silica sol.
[0028] S3. Add tetramethylammonium hydroxide, a catalyst for assisting gelation, to the silica sol and stir evenly, then pour into a mold and react at 60°C for 45 minutes to obtain a gelled wet gel; wherein the mass ratio of tetramethylammonium hydroxide to silica sol is 0.005:1. Stand for 12 hours to demould, and soak in ethanol for aging, wherein the aging temperature is 65°C and the aging time is 48 hours. Finally, use supercritical CO 2 Drying to obtain large-sized SiO 2 Aerogel composite plate sample 1, in which supercritical CO 2 Drying parameters are as follows: drying pressure is 8MPa, CO 2 The flow rate is 2500kg / h, the drying temperature is 55℃, and the drying time is 72h. The performance is shown in Table 1 Sample 1. Example 3
[0029] This embodiment provides a large-size flexible SiO 2 The preparation method of the aerogel composite plate comprises the following steps: S1. After 3-(2,3-epoxypropoxy)propyltrimethoxysilane and ricinoleic acid are mixed and stirred at a mass ratio of 1:0.2, sulfuric acid as a catalyst is added and reacted at 120°C for 48 hours to obtain a colorless, transparent and viscous flexible composition. The viscosity of the flexible composition is tested to be 4900 mPa.s and the average molecular weight is 35000.
[0030] S2. The flexible composition, ethanol and water are poured into a container in a mass ratio of 1:7:0.012, mixed and stirred evenly, and then 1 mol / L hydrochloric acid is added to adjust the pH to about 3-4, and hydrolyzed at 60° C. for 8 h to form silica sol.
[0031] S3. Add tetramethylammonium hydroxide, a catalyst for assisting gelation, to the silica sol and stir evenly, then pour into a mold and react at 60°C for 40 minutes to obtain a gelled wet gel; wherein the mass ratio of tetramethylammonium hydroxide to silica sol is 0.005:1. Stand for 12 hours to demould, and soak in ethanol for aging, wherein the aging temperature is 65°C and the aging time is 48 hours. Finally, use supercritical CO 2 Drying to obtain large-sized SiO 2 Aerogel composite plate sample 2, in which supercritical CO 2 Drying parameters are as follows: drying pressure is 8MPa, CO 2 The flow rate is 2500 kg / h, the drying temperature is 55°C, and the drying time is 72 hours. The performance is shown in Table 1 Sample 2. Example 4
[0032] This embodiment provides a large-size flexible SiO 2 The preparation method of the aerogel composite plate comprises the following steps: S1. After 3-(2,3-epoxypropoxy)propyltrimethoxysilane and Y-10 vegetable oil acid are mixed and stirred at a mass ratio of 1:0.2, sulfuric acid as a catalyst is added and reacted at 120°C for 48 hours to obtain a colorless, transparent and viscous flexible composition. The viscosity of the flexible composition is tested to be 5000mPa.s and the average molecular weight is 36000.
[0033] S2. The flexible composition, ethanol and water are poured into a container in a mass ratio of 1:7:0.012, mixed and stirred evenly, and then 1 mol / L hydrochloric acid is added to adjust the pH to about 3-4, and hydrolyzed at 60° C. for 8 h to form silica sol.
[0034] S3. Add tetramethylammonium hydroxide, a catalyst for assisting gelation, to the silica sol and stir evenly, then pour into a mold and react at 60°C for 47 minutes to obtain a gelled wet gel; wherein the mass ratio of tetramethylammonium hydroxide to silica sol is 0.005:1. Stand for 12 hours to demould, and soak in ethanol for aging, wherein the aging temperature is 65°C and the aging time is 48 hours. Finally, use supercritical CO 2 Drying to obtain large-sized SiO 2 Aerogel composite plate sample 3, in which supercritical CO 2 Drying parameters are as follows: drying pressure is 8MPa, CO 2 The flow rate is 2500 kg / h, the drying temperature is 55°C, and the drying time is 72 hours. The performance is shown in Table 1, Sample 3. Example 5
[0035] This embodiment provides a large-size flexible SiO 2 The application of the aerogel composite plate is to use any one of the large-sized flexible SiO 2 Aerogel composite panels are used as sandwich materials for super energy-saving aerogel composite glass products. Comparative Example:
[0036] This comparative example provides a method for preparing SiO 2 The method of aerogel composite board comprises the following steps: Pour tetraethyl orthosilicate, ethanol and water into a container in a mass ratio of 1:7:0.012 and mix and stir evenly. Then add 1 mol / L hydrochloric acid to adjust the pH to about 3-4 and hydrolyze at 60°C for 8 hours to form silica sol. Add the catalyst tetramethylammonium hydroxide to the silica sol and stir evenly. Pour it into a mold and react at 60°C for 47 minutes to obtain a gelled wet gel; wherein the mass ratio of tetramethylammonium hydroxide to silica sol is 0.005:1. Stand for 12 hours to demould, and soak in ethanol for aging, wherein the aging temperature is 65°C and the aging time is 48 hours. Finally, use supercritical CO 2 Dry to obtain SiO 2 Aerogel composite plate sample 4, in which supercritical CO 2 Drying parameters are as follows: drying pressure is 8MPa, CO 2 The flow rate is 2500 kg / h, the drying temperature is 55°C, and the drying time is 72 hours. The performance is shown in Table 1, Sample 4.
[0037] The density, size, thermal conductivity and visible light transmittance of samples 1-4 were tested and recorded respectively. The results are shown in Table 1.
[0038] Table 1 Large size SiO 2 Aerogel composite board performance parameters
[0039] As shown in Table 1, samples 1-3 have relatively large sizes, low density and thermal conductivity, and high light transmittance, while sample 4 is in the form of fragments and does not have a large-size structure. Therefore, it is difficult to obtain large-size SiO 2 Aerogel composite board; By comparing samples 1-4, it can be seen that the SiO 2 The compression strength and impact strength of aerogel composite plates (samples 1-3) are much higher than those of SiO 2 Aerogel composite sheet (Sample 4).
[0040] Other aspects of the present invention that are not described in detail are all conventional techniques known to those skilled in the art.
[0041] It should be noted that the terms "comprises", "includes" or any other variations are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0042] The protection scope of the present invention is not limited to the technical solutions disclosed in the specific implementation methods. Any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A large-size flexible SiO2 aerogel composite board, which is obtained by hydrolyzing the flexible composition, gelling in a mold, demolding, aging and drying, characterized in that The flexible composition is obtained by reacting the epoxy group on the siloxane chain in the silicon source with the carboxyl group of bio-based oleic acid, and grafting a long-chain flexible alkyl chain on the siloxane chain of the silicon source, wherein the silicon source is a bifunctional 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
2. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 1, characterized in that: The following steps are involved: S1. 3-(2,3-epoxypropoxy)propyltrimethoxysilane and bio-based oleic acid were mixed and stirred uniformly in proportion, and then the catalyst 1 for auxiliary grafting was added to react, and a colorless, transparent and viscous flexible composition was obtained after the reaction was completed; S2. The flexible composition, ethanol and water are mixed and stirred in proportion, and hydrochloric acid is added to adjust the pH to 3-4, and hydrolyzed to form a silica sol; S3. Add silica sol to catalyst 2 for assisting gelation and stir evenly, then pour into a mold to react to obtain a gelled wet gel. Then, demold the wet gel and age and dry it to obtain a large-sized SiO2 aerogel composite board.
3. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2, characterized in that The epoxy value of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.25 mol to 0.45 mol / 100 g.
4. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2 is characterized in that The bio-based oleic acid is any one of ricinoleic acid, lauric acid, Y-8 type vegetable oleic acid and Y-10 type vegetable oleic acid, and the acid value of the bio-based oleic acid is 160-175.
5. A large-size flexible SiO2 aerogel composite board and a preparation method thereof according to claim 2, characterized in that: In step S1, the viscosity of the colorless, transparent and viscous flexible composition is 3000mPa.s-5500mPa.s, and the average molecular weight is 22000-38000.
6. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2, characterized in that : The catalyst 1 is any one of sulfuric acid, zinc chloride and nitric acid.
7. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2, characterized in that : In step S1, the mass ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to bio-based oleic acid is 1:(0.05-0.25).
8. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2, characterized in that : In step S2, the mass ratio of the flexible composition, ethanol and water is 1:(5-9):(0.012-0.018).
9. The method for preparing the large-size flexible SiO2 aerogel composite board according to claim 2, characterized in that: The catalyst 2 is any one of ammonia water, tetramethylammonium hydroxide and sodium hydroxide; in step S3, the mass ratio of the catalyst 2 to the silica sol is (0.005-0.02):
1.
10. Application of the large-size flexible SiO2 aerogel composite board according to claims 1-9, characterized in that :The application method is to use the large-size flexible SiO2 aerogel composite board as the sandwich material of super energy-saving aerogel composite glass products.